The Characterization of Active Compound of Pedada Magrove Plants (Sonneratia caseolaris) Which HaveThePotential as Natural Antioxidants - Latief, Madyawati (Talenta Publisher, 2019)
The present research aimedto isolate the compound from the acetone fractions of pedada leaves (Sonneratia caseolaris) and test its antioxidant activity. The extraction wasperformed usinga multi-stage maceration method. The separation and purification were done using a vacuum and gravitational column chromatography whereasthe antioxidant activity was tested with theDPPH method. The structural elucidation of the compound was performed by spectroscopy data of UV, IR, alsoone- and two-dimensional NMR. The appearance of the pure isolate was odorless yellow crystal. Based on the spectroscopy data, the compound wasstigmasta-5,22-dien-3-ol. The activity testing of the extract antioxidant and pure isolate with IC50showed a value of 166.2 ppm dan 134.4 ppm, respectively.